Text coverless information hiding method based on synonyms expansion and label delivery mechanism - Zhen ZHANG; Jiaming NI; Ye YAO; Lichun GONG; Yujuan WANG; Guohua WU (Tongxin xuebao)
To solve the problems of low hiding capacity and weak detection resistance, a method of coverless information hiding based on synonyms expansion and label delivery mechanism was proposed.To begin the proposed method, the secret information were divided into several keywords, then those keywords were embedded in different carrier texts respectively.Considering the interchangeability of synonyms in Chinese, using the word similarity calculation method based on HowNet,it was possible to filter synonyms which met the contextual semantics.For the purpose of increasing hiding capacity, various keywords or their synonyms were embedded in the same carrier text as much as possible.At the same moment, when recording the positional parameters of the secret information in each carrier text, those parameters were converted into a binary sequence in a fixed format, which was used to generate carrier text.Finally, the carrier texts and generated text were sent to the receiver.Comparison of the results with those of other studies confirm that the proposed method not only makes great improvement in hiding capacity and detection resistance, but also reduces the overhead of establishing and maintaining databases by using small text database.